Hong Kong Invaded! : A 'Ninety-Seven Nightmare - Bickley, Gillian, 1943- (Book collections on Project MUSE., 2001)
This visionary novel by an anonymous author has been forgotten for a hundred years. Yet when published as The Back Door during the negotiations between Imperial China and Great Britain over the lease of the New Territories, the story aroused serious British fears about the possibility of defending Hong Kong against attack.